2010
DOI: 10.1210/jc.2009-2675
|View full text |Cite
|
Sign up to set email alerts
|

LMNArs4641 and the Muscle Lamin A and C Isoforms in Twins—Metabolic Implications and Transcriptional Regulation

Abstract: The LMNA rs4641 T-allele is associated with increased LBM and FM with more fat relative to muscle in elderly twins, which may impact risk of type 2 diabetes. Increased mRNA levels of lamins with age may counteract muscle wasting, and influence of insulin on lamin A-to-C ratio suggests a role in cytoskeletal muscle protein regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This LMNA SNP is located in exon 10, at the physiological splice site of LMNA pre-mRNAs, whose use by the splicing machinery leads to the production of prelamin A rather than 'by default' lamin C-encoding mRNAs. This SNP was previously variably reported to influence [24][25][26] or not 27-29 the disease severity and lamin A/C expression levels. 20 We first checked the possibility in cis association of one of the SNP alleles with the LMNA mutations, and found none.…”
Section: Discussionmentioning
confidence: 85%
“…This LMNA SNP is located in exon 10, at the physiological splice site of LMNA pre-mRNAs, whose use by the splicing machinery leads to the production of prelamin A rather than 'by default' lamin C-encoding mRNAs. This SNP was previously variably reported to influence [24][25][26] or not 27-29 the disease severity and lamin A/C expression levels. 20 We first checked the possibility in cis association of one of the SNP alleles with the LMNA mutations, and found none.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, Miranda et al (2008) observed altered lamin A to lamin C mRNA ratio in both obesity and type 2 diabetes. Noteworthy, insulin has been suggested to have an influence on lamin A to lamin C mRNA ratio (Wegner et al 2010). Acute insulin stimulation was shown to increase lamin A mRNA, whereas lamin C mRNA was decreased in skeletal muscle biopsies from young and elderly twins carrying a polymorphism in LMNA (Wegner et al 2010).…”
Section: Altered Lamin a To Lamin C Expression Ratio In Diseasesmentioning
confidence: 99%
“…Noteworthy, insulin has been suggested to have an influence on lamin A to lamin C mRNA ratio (Wegner et al 2010). Acute insulin stimulation was shown to increase lamin A mRNA, whereas lamin C mRNA was decreased in skeletal muscle biopsies from young and elderly twins carrying a polymorphism in LMNA (Wegner et al 2010). It is important to note that there is evidence that disruption of the balance between the major A-type lamin isoforms at the transcript or protein levels may lead to human diseases.…”
Section: Altered Lamin a To Lamin C Expression Ratio In Diseasesmentioning
confidence: 99%
“…The second condition could be a lamin A/C mutation or a multisystem metabolic defect with the myocardium being predominantly affected. Whether the LMNA polymorphism rs4641 (c.1698C>T; p.H566H) was responsible for the variable phenotype remains speculative, but previous studies have shown that this SNP is associated with an increased risk to develop diabetes [9,10]. Arguments for a metabolic defect are the combination of dCMP, thrombopenia, hypothyroidism, diverticulosis, liver hemangiomas, the double kidney and the repeatedly elevated serum lactate levels.…”
Section: Discussionmentioning
confidence: 99%